Cover Picture: Raman Under Water – Nonlinear and Nearfield Approaches for Electrochemical Surface Science (ChemElectroChem 8/2017). Issue 8 (28th June 2017) - Martín Sabanés, Natalia; Domke, Katrin F.
Abstract : The Front Cover picture is a cartoon association with Raman under water, depicting an underwater scene where molecule‐plants attached to nearfield‐generating particles are illuminated by a spotlight of a submarine and studied through a periscope More information can be found in the Minireview by N. M. Sabanés and K. F. Domke onpage 1814 in Issue 8, 2017 (DOI:10.1002/celc.201700293 ).